Network Reconfiguration for Loss Reduction and Voltage Profile Improvement of 110-Bus Radial Distribution System Using Exhaustive Search Techniques - Su Mon Myint; Soe Win Naing (Institute of Advanced Engineering and Science, 2015)
Nowadays, the electricity demand is increasing day by day and hence it is very important not only to extract electrical energy from all possible new power resources but also to reduce power losses to an acceptable minimum level in the existing distribution networks where a large amount of power dissipation occurred. In Myanmar, a lot of power is remarkably dissipated in distribution system. Among methods in reducing power losses, network reconfiguration method is employed for loss minimization and exhaustive technique is also applied to achieve the minimal loss switching scheme. Network reconfiguration in distribution systems is performed by opening sectionalizing switches and closing tie switches of the network for loss reduction and voltage profile improvement. The distribution network for existing and reconfiguration conditions are modelled and simulated by Electrical Transient Analyzer Program (ETAP) 7.5 version software. The inputs are given based on the real time data collected from 33/11kV substations under Yangon Electricity Supply Board (YESB). The proposed method is tested on 110-Bus, overhead AC radial distribution network of Dagon Seikkan Township since it is long-length, overloaded lines and high level of power dissipation is occurred in this system. According to simulation results of load flow analysis, voltage profile enhancement and power loss reduction for proposed system are revealed in this paper.